2013
DOI: 10.1093/ntr/ntt095
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of How Young Scottish Smokers Living in Disadvantaged Communities Get Their Cigarettes

Abstract: introduction: Reducing access to cigarettes is an important element of youth smoking prevention strategies. This is particularly so in disadvantaged communities that have high rates of youth smoking. In 2010, Scotland banned proxy sales of tobacco products to under 18-year-olds who were getting older people to purchase cigarettes on their behalf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…In both UK and Australian studies, some parents reported refusing to facilitate their children's smoking until they were 16 or older,47 51 suggesting that legislative measures have a normative effect, even in contexts of high prevalence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both UK and Australian studies, some parents reported refusing to facilitate their children's smoking until they were 16 or older,47 51 suggesting that legislative measures have a normative effect, even in contexts of high prevalence.…”
Section: Resultsmentioning
confidence: 99%
“…The nexus between smoking, cannabis and alcohol was touched on in several other studies,47 51 52 with all three to varying degrees constituting a major social activity, often done on the streets due to an absence of other leisure options.…”
Section: Resultsmentioning
confidence: 99%
“…Also, low SES adolescents in our sample had a lower personal income on average, so that it is unlikely that cigarettes were more affordable in this group. A recent qualitative study on Scottish adolescents from deprived areas suggested that some adolescents received money from their parents specifically to buy cigarettes, which adolescents may not view as personal income 37. A recent paper also showed that low SES adolescents were more exposed to smoking by their friends 26, so that the exchange of cigarettes may be more common in that group, attenuating the influence of personal income.…”
Section: Discussionmentioning
confidence: 99%
“…Our study reveals that well over 60% of students get cigarettes by buying or receive from friends and relatives. Other studies show the same results (Hughes et al, 2011, Leatherdale et al, 2011, Marsh et al, 2012, Donaghy et al, 2013) that illegal commercials, friends, relatives, and strangers are considered as sources of providing cigarettes for the students. It suggests that monitoring of law enforcement at the shops selling products-related tobacco is of vital importance.…”
Section: Discussionmentioning
confidence: 66%